How Self-Efficacy and Husnuzan Towards Allah Shape Future Anxiety Among Students: A Quantitative Study - Cahyani, Putri; Syukrilla, Wara Alfa; Nihayah, Zahrotun (Psikoislamika: Jurnal Psikologi Islam, 2025)
Future anxiety can reduce quality of life, affecting happiness, satisfaction, and reaching goals. Constant worry can make it hard to enjoy daily life and may lead to stress, depression, and poor physical health. This study aims to examine the influence of self-efficacy, husnuzan, and social support on the future anxiety of students. This study used a quantitative approach cross-sectionally with multiple regression analysis. The sample consisted of 204 students (M=20.69, SD=1.21, female=149, male=55 )at State Islamic University Jakarta selected using accidental sampling.  Instruments used in this study were the Future Anxiety Scale, NGSE Scale, Husnuzan Scale, and social support scale developed according to Sarafino (2011). Confirmatory Factor Analysis was used to test the construct validity of the instruments. Self-efficacy (β =  0.209, p 0.000) and husnuzan towards Allah (β = 0.486, p 0.000) have been proven to be significant protective factors for future anxiety among students with R2=0.398 (F(7,196)=18.5, p0.000). These findings suggest that students should develop strategies to increase their self-efficacy and encourage a husnuzan attitude towards Allah.